Expression of Neuron-Specific Enolase and Other Neuroendocrine Markers is Correlated with Prognosis and Response to Therapy in Non-Hodgkin Lymphoma - Chowdhury, Somshankar; Kataria, S.P; Yadav, Amit Kumar (Journal of Laboratory Physicians, 2022)
Objective Non-Hodgkin lymphoma (NHL) is a common hematological malignancy. There is very little known about the expression of neuroendocrine immunohistochemical markers and their clinical significance in NHL due to the paucity of studies. Our objective was to study the expression of neuroendocrine immunohistochemical markers in NHL and correlate with clinical parameters.Materials and Methods All cases diagnosed as NHL on morphology and immunohistochemistry (World Health Organization, 2016 classification) were included in the study. Immunohistochemistry for neuron-specific enolase (NSE), synaptophysin, and chromogranin A was performed. The results were correlated with clinical parameters and response to chemotherapy.Results A total of 66 cases were included in the study with a male-to-female ratio of 3.1:1. The most frequent subtypes observed were diffuse large B-cell lymphoma not otherwise specified and follicular lymphoma. Among the neuroendocrine markers, positivity was observed only for NSE, whereas the other markers were uniformly negative. It was positive in both B- and T-cell lymphomas and in many different subtypes. No relation with the age and sex of the patients was observed. However, NSE-positive cases, more frequently, presented in the advanced stage as compared with NSE negative (61 vs. 38%). All NSE-positive cases showed remission with chemotherapy.Conclusion Among the neuroendocrine immunohistochemical markers, positivity was observed only for NSE. This isolated positivity suggests cross-binding of NSE antibodies with some other isoenzyme of NSE. NSE positivity was associated with higher stage and better response to therapy. Despite this apparent paradox, it is recommended that NSE should be part of routine immunohistochemical panel for NHL.
Keywords: Immunohistochemical markers; Lymphoma; Neuroendocrine; Neuron-specific enolase; Non-Hodgkin